How Did It Happen: Organizational Commitment and Work-Life Balance Affect Organizational Citizenship Behavior - Soelton, Mochamad (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
Schools as educational institutions are expected to be able to produce quality human resources and are supported by high teacher competence, teachers must be reliable and must appear professional to be able to give birth to future generations who are intelligent and have character. This study aims to analyze the effect of Organizational Commitment and Work-Life Balance on Organizational Citi- zenship Behavior through Learning Organization mediation in elementary school teachers in West Jakarta. The sampling of 72 teachers was saturated, and the analysis was carried out quantitatively us- ing the questionnaire method and using the Structural Equation Model (SEM) with the Smart–PLS analysis method. The conclusion of the research Organizational Commitment and Work-Life Bal- ance has a significant positive effect on Organizational Citizenship Behavior, Organizational Com- mitment and Work-Life Balance have a significant positive effect on Learning Organization, Learn- ing Organizations have a significant positive effect on Organizational Citizenship Behavior. Learning Organization is not able to mediate the effect of Organizational Commitment on Organizational Citizenship Behavior as well as Learning Organization is not able to mediate the effect of Work-Life Balance on Organizational Citizenship Behavior.